Association between stress, body weight status and metabolic syndrome among adult population in Terengganu - Miow, Y.X.; Wee, B.S.; Karimah Fakhriah, I.; Aryati, A. (2018)
Metabolic syndrome (MetS) is a clustering of cardiovascular risk factors including central obesity, dyslipidemia, insulin resistance and hypertension. Presence of stress and MetS are believed to be significant in adults nowadays. Nevertheless, there is still limited data on association between stress and MetS to confirm this among adult population in sub-urban state like Terengganu. Therefore, this study aimed to investigate the association between stress and MetS among adult population in Terengganu. A cross-sectional study was conducted among 188 adults aged 20 to 59 years old in Terengganu. A self-administered questionnaire was used to obtain data on sociodemographic characteristics. Anthropometric and biochemical parameters comprised of weight, height, waist circumference, fasting blood glucose, blood lipid profile and blood pressure were measured. Stress level was assessed using Depression, Anxiety and Stress Scale-21. Joint Interim Statement (2009) on MetS was used to identify MetS. Subjects were 79.3% Malays (n=149), 4.8% Chinese (n=9) and 16.0% Indians (n=30). Of that, 39.4% were males whilst 76.6% were females. The prevalence of stress and MetS was 17.6% and 39.4% respectively. There was no significant association between gender, age, ethnicity, body weight status and MetS with stress. In addition, there was no significant association between gender, age, ethnicity and stress with MetS. However, there was a significant association between body weight status and MetS. Binary logistics regression showed that the odds of developing MetS were 9.1 (95% CI: 2.0 – 41.1) and 16.8 (95% CI: 3.8 – 74.8) times higher in overweight and obese subjects respectively. Surprisingly, no significant association between stress and MetS was found. This finding conflicted with those studies that supported this association. This conflicting result might be contributed by self-report bias and tendency of subjects reporting a socially desirable response. This study showed no significant association between stress and MetS among adult population in Terengganu. Prospective cohort study is required to identify significant psychological risk factor of MetS among this population.